A cost-effectiveness analysis of fuel cell electric vehicles considering infrastructure costs and greenhouse gas emissions: An empirical case study in Korea. (December 2022) - Moon, Saedaseul; Lee, Yeon-Jeong; Lee, Deok-Joo
Highlights: A cost-effectiveness analysis is conducted for fuel cell electric vehicle. Charging and refueling infrastructure costs are considered. Further technological advance is required even for by-product hydrogen vehicles. 72.3% of purchase cost needs to be reduced for cost-effectiveness. Naphtha-cracking tube-trailer combination is the most viable infrastructure option. Abstract: A cost-effectiveness analysis was applied to compare the costs of reducing greenhouse gas emissions by switching to vehicles powered by alternative fuels. We adopted a total cost of ownership analysis to determine the switching costs, and a well-to-wheel analysis to calculate the quantity of greenhouse gases eliminated. We included the costs of the charging infrastructure, which is indispensable for both electric vehicles and fuel cell electric vehicles. We conducted a case study in the South Korean market, where fuel cell vehicles are more common than in most other countries. We found that even vehicles that run on by-product hydrogen require further technological advances to achieve cost-effectiveness despite their relatively low environmental impact. In terms of purchase cost, fuel cell vehicles require a 72.3% reduction to achieve cost-effectiveness, while battery-powered electric vehicles require a 45.3% reduction. Both on-site steam methane reforming and a combination of steam methane reforming and pipeline delivery of hydrogen were less cost-effective than a naphtha-cracking tube-trailer combination in terms of infrastructure costs, despite low transportation costs. Electrolysis of hydrogen was not as economically feasible and produced more greenhouse gases compared to battery-powered electric vehicles.